UJI MUTU FISIK SERUM GEL KOMBINASI EKSTRAK ETANOL DAUN KOPI ARABIKA (Coffea arabica L.) DAN MADU HUTAN (Apis dorsata) SERTA UJI AKTIVITAS ANTIBAKTERI TERHADAP BAKTERI Propionibacterium acnes - Noni Rahayu Putri; Yahdian Rasyadi; Ramiza Jihan Fadillah (Nusantara Hasana Journal, 2024)
The flavonoids contained in the ethanolic extract of arabica coffee (Coffea arabica L.) and forest honey (Apis dorsata) leaves have high acidity, high reducing sugar content and have potential as antibacterial. This study aimed to see if serum gel preparations could be formulated from a combination of ethanolic extract of arabica coffee leaves with forest honey and to see antibacterial activity against Propionibacterium acnes bacteria. Serum gel is made in 4 formulas, F0(0%), F1(10%), F2(20%) and F3(30%). Then the physical tests carried out include organoleptic examination, pH test, homogeneity, viscosity test and stability test. The antibacterial activity test against the propionibacterium acnes bacteria was carried out using the well method. All gel serum formulas provide physical test results that meet the requirements and are stable. The antibacterial activity test on F0 did not provide an inhibitory zone, F1 was in the medium category (8 mm), F2 was in the strong category (16.7 mm) and F3 was in the very strong category (23.3 mm). A combination of ethanol extract of Arabica coffee leaves and forest honey can be made in the form of a serum gel preparation. The most effective formula against Propionibacteriun acnes bacteria is F3.